2018
DOI: 10.1002/rmv.2013
|View full text |Cite
|
Sign up to set email alerts
|

Orf virus: A promising new therapeutic agent

Abstract: Summary The orf virus (ORFV) is a zoonotic, epitheliotropic, DNA parapoxvirus that infects principally sheep and goats. Exposure of animals to the virus or immunization by an ORFV preparation can accentuate the severity of disease, which has provoked an interest in the underlying cellular, virological, and molecular mechanisms. The identified ORFV virulence genes and the fact that the virus can repeatedly infect a host, owing to its evasive mechanisms, contribute to the development of potent immune modulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 92 publications
(157 reference statements)
0
30
0
Order By: Relevance
“…Previously, we reported the successful use of the attenuated ORFV for the generation of different recombinants with diverse modifications able to protect against various infectious viral diseases ( Rohde et al, 2011 , 2013 ; Rziha et al, 2016 ; van Rooij et al, 2010 ). Also other ORFV strains were successfully used for the generation of recombinant vaccines ( Hain et al, 2016 ; Tan et al, 2012 ), and inactivated ORFV showed immunomodulatory properties in different preclinical models ( Bergqvist et al, 2017 ; Fleming et al, 2015 ; Wang et al, 2019 ). Furthermore, Rintoul et al demonstrated an oncolytic activity for the wild-type ORFV strain NZ2, causing a significantly reduced tumor growth in immune-competent and xenograft human tumor models ( Rintoul et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported the successful use of the attenuated ORFV for the generation of different recombinants with diverse modifications able to protect against various infectious viral diseases ( Rohde et al, 2011 , 2013 ; Rziha et al, 2016 ; van Rooij et al, 2010 ). Also other ORFV strains were successfully used for the generation of recombinant vaccines ( Hain et al, 2016 ; Tan et al, 2012 ), and inactivated ORFV showed immunomodulatory properties in different preclinical models ( Bergqvist et al, 2017 ; Fleming et al, 2015 ; Wang et al, 2019 ). Furthermore, Rintoul et al demonstrated an oncolytic activity for the wild-type ORFV strain NZ2, causing a significantly reduced tumor growth in immune-competent and xenograft human tumor models ( Rintoul et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on ORFV production processes is very limited and mainly focuses on upstream processing ( Pohlscheidt et al, 2008 ; Wang et al, 2019 ). Downstream processing (DSP) procedures generally employ sucrose gradient ultracentrifugation ( Rziha et al, 2016 ) and do not satisfy regulatory demands for the purity of vaccines and gene therapeutic products ( European Pharmacopoeia, 2020 ; World Health Organization, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in virulence and pathogenesis are distributed in the ITR regions of the ORFV genome. The virus encodes involved in immunomodulation, including viral-interleukin 10 (vIL-10, ORFV127), vascular endothelial growth factor (VEGF, ORFV132), orf virus interferon resistance protein (OVIFNR, ORFV020), chemokine binding protein (CBP, ORFV112), granulocyte-macrophage colony-stimulating factor/interleukin-2 (GM-CSF/IL-2) inhibitory protein (GIF, ORFV117), nuclear factor kappa B (NF-κB) inhibitory protein (ORFV125), and deoxyuridine 5′-triphosphate pyrophosphatase (dUTPase, ORFV007) [38].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a newly generated set of Orf virus (ORFV; family Poxviridae) vector vaccines [18] expressing PaBV-4 N and P was included. ORFV-based recombinant vector vaccines have been successfully applied in a broad range of species [19][20][21], including efficient protection of rats against experimental BoDV-1 infection [13,22].…”
Section: Introductionmentioning
confidence: 99%